Advancements in Material Science: Exploring Natural Rubbers, Nanocomposites, Blends, and Alloys - Sharma, Shivam (Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
This article delves into the cutting-edge developments in material science, focusing on natural rubbers and their transformation through the integration of nanocomposites, blends, and alloys. Natural rubbers, derived from rubber trees, have long been utilized in industries worldwide, but their inherent limitations prompted researchers to seek innovative solutions. The incorporation of nanofillers into rubber matrices has led to the emergence of high-performance nanocomposites, enhancing mechanical and thermal properties. Additionally, polymer blends, combining natural and synthetic rubbers, offer a versatile approach to tailoring material characteristics for specific applications. The article also explores rubber alloys, where the fusion of rubber with non-rubber materials yields materials with unique elasticity and structural integrity. Through these advancements, researchers aim to revolutionize industries such as automotive, healthcare, and consumer goods, creating materials that are not only high-performing but also environmentally sustainable.